Determinants of Tax Avoidance: Evidance on Indonesian Financial Companies - Wulandari, Sartika; Oktaviani, Rachmawati Meita; Jaeni, Jaeni (Owner : Riset dan Jurnal Akuntansi, 2024)
Tax avoidance by companies is a risky strategy that aims to minimize corporate taxes on pre-tax profits. This study aims to provide empirical evidence regarding the effect of audit committees, independent commissioners, liquidity, leverage, company size, and profitability on tax avoidance and examine differences in tax avoidance before and during the COVID-19 pandemic. The population in this study was financial sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. Using a purposive sampling technique, data were obtained from 42 companies, so 168 observations were gained. The data analysis technique utilized EViews version 12. The results of this study demonstrated that while independent commissioners could suppress tax avoidance, another corporate governance proxy, i.e., the audit committee, did not affect tax avoidance. Furthermore, liquidity and firm size did not affect tax avoidance, whereas leverage and profitability positively affected tax avoidance. Before and during the COVID-19 pandemic, no difference between tax avoidance practices was visible.